2005
DOI: 10.1002/hbm.20103
|View full text |Cite
|
Sign up to set email alerts
|

Using automated morphometry to detect associations between ERP latency and structural brain MRI in normal adults

Abstract: Despite the clinical significance of event-related potential (ERP) latency abnormalities, little attention has focused on the anatomic substrate of latency variability. Volume conduction models do not identify the anatomy responsible for delayed neural transmission between neural sources. To explore the anatomic substrate of ERP latency variability in normal adults using automated measures derived from magnetic resonance imaging (MRI), ERPs were recorded in the visual three-stimulus oddball task in 59 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 83 publications
2
22
0
Order By: Relevance
“…In line with these neuroanatomic considerations, 2 independent studies found that P300 amplitude and latency were positively correlated with the corpus callosum volume. 29,56 There is further evidence indicating a positive correlation between anisotropy values of the genu and P300 measures during a continuous performance test. 30 Second, we uncovered a positive association between P300 amplitude and the white matter volume underlying the right supramarginal gyrus extending into the right arcuate fasciculus.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In line with these neuroanatomic considerations, 2 independent studies found that P300 amplitude and latency were positively correlated with the corpus callosum volume. 29,56 There is further evidence indicating a positive correlation between anisotropy values of the genu and P300 measures during a continuous performance test. 30 Second, we uncovered a positive association between P300 amplitude and the white matter volume underlying the right supramarginal gyrus extending into the right arcuate fasciculus.…”
Section: Discussionmentioning
confidence: 94%
“…27,28 Disruption of white matter tracts may thus alter the electrophysiologic response and perturb brain connectivity during the prepsychotic phases. A combined event-related potential (ERP) and magnetic resonance imaging (MRI) study in healthy adults has confirmed significant correlations between P300 measures and white matter contractions, 29 whereas a recent study involving patients presenting with a first episode of psychosis has found specific correlations between anisotropy values and P300 measures. 30 Although there is independent evidence indicating both P300 and white matter alterations in patients at risk for psychosis, no formal study has properly tested the putative relation of these factors during the prepsychotic phases.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of a change in amplitude may suggest that BMIP and PH are less reliably associated with gray matter dysfunction, indexed primarily by ERP amplitude, than with white matter dysfunction, indexed primarily by ERP latency [47] . Indeed, white matter abnormalities do appear to be the predomi- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this initial work we have used a single reference anatomy which was manually partitioned into left and right hemispheres. A multi-resolution B-Spline based spatial normalization, adapted from that described in [Studholme et al, 2004b,a] and as used in [Cardenas et al, 2005], was then applied to estimate a spatial transformation mapping from this reference to each subject MRI being studied. This transformation was then numerically inverted to allow the assignment of the nearest reference label to a given subject image voxel, which brought the voxelwize partitioning of the reference anatomy to the same space as the surface extracted from each infant.…”
Section: Corticalmentioning
confidence: 99%